Bedre samhandling – er løsningen nye arenaer? - Hansen, Gunnar Vold; Ramsdal, Helge (Nordisk tidsskrift for helseforskning, 2014)
This article discusses the challenges facing service provision for people with simultaneous addiction and severe mental health problems (ROP-patients). Based on a mid-term evaluation of a project intended to improve collaboration and coordination of services for the patient group we discuss different approaches to analyse service organisations from an organisation theoretical perspective. One of the findings is that it will give new insights if approaching these challenges as “wicked problems”. Here we find that a non-linear approach, organised as an interaction between patients’ and professionals’ experience, data gathering and organisation analysis will offer a more comprehensive understanding on how to improve services than a linear, rational decision process.